My partner and my neighbourhood: The built environment and social networks' impact on alcohol consumption during early pregnancy. (January 2020) - Ortega-García, Juan A.; López-Hernández, Fernando A.; Azurmendi Funes, Maria Luisa; Sánchez Sauco, Miguel F.; Ramis, Rebeca
Abstract: Maternal alcohol consumption during pregnancy is responsible for negative health outcomes. The literature shows that socio-economic and lifestyle factors are both related with alcohol consumption during pregnancy; nevertheless, the role of other factors is unclear. The objective of this study is to assess the role that partners' alcohol consumption plays, that played by accessibility to alcohol, and by social influence – when considering pregnant women's behaviour as regards alcohol. It presents the results from a follow-up study of children at risk of negative health outcomes associated with prenatal alcohol exposure; it shows that 68% of pregnant women included in the study reported alcohol consumption during early pregnancy. Results of the analysis showed association with partners' alcohol use, with density of bars and/or restaurants and with the number of pregnant women who drank in the neighbourhood. We concluded that the involvement of men in pregnancy healthcare, and urban policies which target the built environment and improve social networks could be important aspects for the control and prevention alcohol consumption during pregnancy in public health programs. Interventions and recommendations should include an ecological perspective on prenatal community-health programs – focusing on individual, social, and natural factors as well as the built environment. Highlights: - Despite recommendations about avoiding alcohol consumption during pregnancy, a significant number of women still drink when they are pregnant. - In addition to individual factors the partner's alcohol consumption has an important effect on the probability of pregnant women consuming alcohol. - Determinants of alcohol consumption probability include: social interaction of pregnant women with their partners, with people in the neighbourhood in bars and restaurants, and with other pregnant women.